An examination of the effect of the global financial crisis on the link between capital structure and firm performance - Malekanyo, Reoagile (Department of Finance and Tax, 2024)
The study examines the effect of the global financial crisis on the link between capital structure and firm performance using panel data of the South African nonfinancial firms that were listed on the Johannesburg stock exchange (JSE) for the period between 2007 and 2012. The analysis is done by splitting the entire period into the during and post financial crisis and then combining the two datasets after controlling for the period type to examine if the crisis period had an impact on the link between capital structure and firm performance. The relationship is examined based on two prominent capital structure theories, that is, the trade-off theory and perking order theory. The perking order theory assumes that a negative link exists whereas the trade-off theory assumes that a positive relationship exists. ROA is used as a proxy for firm performance. The ratios of total liabilities, long term liabilities and short-term liabilities to total assets are used as proxies for capital structure. The study uses firm size, liquidity, and tangibility as control variables. The main findings based on the link between capital structure and firm performance show that there was an insignificant negative relationship between firm performance and all proxies of debt, that is, total debt, long term debt and short-term debt during the global financial crisis period while a strong statistically significant negative relationship existed between firm performance and both total debt and long-term debt after the global financial crisis and even after controlling for the period type. The relationship was much stronger with long term debt than with total debt. In contrast, the findings of this study show that there was no significant relationship between short term debt and firm performance during and after the global financial crisis and even after controlling for the period type. The findings of a negative relationship between firm performance and both total debt and long-term debt is consistent with the perking order theory. However, although the results show that the effect of the financial crisis was insignificant, controlling for the effect of the crisis period actually improved the link between capital structure and firm performance as the adjusted Rsquared improved after controlling for the effect of the crisis period. The results also show that there was a significant negative relationship between firm size and performance for all the models considered and that the relationship was stronger after the financial crisis and even after controlling for the period type. Furthermore, the results show that there was a strong and significant positive relationship between liquidity and firm performance for all the models, even after controlling for the period type as well. Lastly, the results of this study show a negative link between tangibility and firm performance for all the models but that the relationship was significant only after the financial crisis period and for the combined period that controls for the period type. Overall, the results in Models 5 and 6 show that although the effect of the global financial crisis was insignificant, controlling for it improved the link between capital structure and firm performance as shown by the improvement in the adjust R-squared.